Is the Connection Between Religiosity and Psychological Functioning Due to Religion's Social Value?: a Failure to Replicate - Pirutinsky, Steven (Journal of religion and health, 2013)
Increasingly, religion and spirituality has been tied to well-being. However, the mediators are likely multifold, contextually dependent, and remain unclear. A recent report suggested that this is due to religion's social value and presented results indicating that religiosity was more strongly related to psychological adjustment within countries with higher mean religiosity. Effect sizes were small, and given previous research suggesting other more proximal mediators, it was my hypothesis that these findings would not be replicated. Analysis of data from the European Social Survey revealed no significant interactions between country-level religiosity and individual religiosity in predicting psychological well-being. These conflicting findings point to the nuanced nature of the religion-health relationship and suggest that this correlation is unlikely to be due to social valuation. Studies using cursory measures are likely to explain only a small proportion of the variance, yield contradictory findings, and fail to significantly enhance theory in this domain.